Fuel properties and steam reactivity of solid waste streams from contingency bases. (August 2018) - Cui, Hong; Turn, Scott
Highlights: Composite waste fuels were prepared for characterizing fuel property and reactivity. Characterization of the composite fuels can be predicted by individual components. A simple methodology for characterizing multi-component solid wastes was validated. Plastic components increase carbon content and HHV of solid waste fuels. Effects of fuel composition on syngas production and composition were explored. Abstract: The solid waste generated from military contingency bases (CBs) is a potential fuel for appropriately-scaled, waste to energy (WTE) systems. To inform WTE system design, fuel properties of seventeen components of synthetic contingency-base waste recipes from the literature were characterized for ultimate analysis, heating values, proximate analysis and reactivity in a steam atmosphere at three temperature typical of gasification conditions. A simple mathematical approach was applied to predict the properties and reactive behavior of composite mixtures using the weighted sum of the corresponding components, assuming negligible interaction between components. The method was validated using prepared composite mixture samples. In addition, chemical equilibrium calculations for steam gasification of the composite samples were conducted to explore the effects of waste composition variability on syngas production and composition.